Exploring Students’ Perceptions of Using Tiktok to Support English Speaking Learning - Laililajri, Kusumanisa Hamassari; Syahid, Abdul; Qamariah, Zaitun (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2025)
This study aimed to explore students’ perceptions of using TikTok as an online learning platform to improve English speaking skills. The background of this research was based on the importance of mastering speaking skills in English as a productive skill that supports communication and academic achievement. With the rapid development of the digital era and the increasing use of social media among students, TikTok was perceived to have potential as an innovative learning medium by providing engaging, easily accessible audio-visual content aligned with the preferences of younger generations. This study employed a qualitative approach using a case study design, which was conducted in an eighth-grade class at a Madrasah Tsanawiyah in Palangka Raya, Central Kalimantan. Data were collected through in-depth interviews with six purposively selected students based on specific criteria. The findings revealed that the majority of students held positive perceptions of using TikTok for learning English speaking skills. They stated that the educational content available on TikTok helped enrich their vocabulary, improve their pronunciation, and increase their learning motivation due to its enjoyable and accessible nature. However, some students expressed neutral to less positive perceptions, preferring traditional learning methods and noting the limitations of TikTok's algorithm, which did not consistently present educational content. In conclusion, TikTok showed potential as a medium for learning English speaking skills, especially when supported by appropriate instructional strategies